2020
DOI: 10.1109/access.2020.2973173
|View full text |Cite
|
Sign up to set email alerts
|

Compliant Control of Single Tendon-Sheath Actuators Applied to a Robotic Manipulator

Abstract: Tendon-sheath actuators (TSAs), similar to Bowden cable-based series elastic actuators (SEAs), have a wide range of applications in robots. However, when applying them to manipulators, force sensors cannot be mounted due to limited space. Therefore, this paper proposes a new method for compliant control based on a dual encoder, and the existing transmission model was improved by considering the joint torque. To validate the proposed method, experimental setups composed of a motor, a tendonsheath component, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The faster of signals are, the more non-linear and hysteresis have been performed. This may be due to the fact that the response characteristics of the Bowden cable determine the output characteristics of the model, which is a problem that many previous studies [32,33] have also encountered. Hence, it should consider the signal frequency when the Bowden cable system has been utilized to the transmission system with continuously changing requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The faster of signals are, the more non-linear and hysteresis have been performed. This may be due to the fact that the response characteristics of the Bowden cable determine the output characteristics of the model, which is a problem that many previous studies [32,33] have also encountered. Hence, it should consider the signal frequency when the Bowden cable system has been utilized to the transmission system with continuously changing requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the position parameters of the joint parts [5] is based on independent measurements using dual encoders mounted on the drive motor and the drive joint. In addition, in [6] it is proposed to calibrate manipulator positions by QR code.…”
Section: Analysis Of Recent Studies and Publicationsmentioning
confidence: 99%
“…The nonlinear friction in the Bowden inner cable and outer sheath is amajor source of hysteresis and phase delay of the transmission system. Studies have shown that a significant amount of the motor torque is generated to overcome the friction of the Bowden transmission cable [ 19 ].One way to address this problem is to use servo motors with very high power output and fast responses, which could reduce the influence of frictional disturbance of the Bowden cables to some extent, even when a basic PID controller is used. Such an approach, however, usually requires a large off-board platform to mount the bulkyservo motors and amplifiers, which prevents the outdoor and portable application of the soft exoskeleton system [ 20 ].…”
Section: Introductionmentioning
confidence: 99%